Preparation and ftir studies of PMMA/PVC polymer blends, PVC-g-PMMA graft copolymers and evaluating graft content - Tham, Do Quang; Mai, Tran Thi; Hoang, Thai; Trang, Nguyen Thi Thu; Chinh, Nguyen Thuy; Thang, Dam Xuan (Vietnam Journal of Science and Technology, 2019)
This study presents the qualitative and quantitative analyses of Fourier Transform Infrared (FTIR) spectra of poly(methyl methacrylate)/poly(vinyl chloride) blends (PMMA/PVC), as well as PVC-g-PMMA graft copolymers. Graft copolymerizations of methyl mathacrylate (MMA) onto PVC macromolecules were carried out mixture of cyclohexanone/N,N-dimethylformamide as solvents, dibenzoyl peroxide as initiator and nitrogen medium. FTIR spectra of PMMA/PVC blends showed that there were molecular interactions between C=O groups of PMMA and C-Cl groups of PVC. Assignments of infrared absorption bands for specific groups of PMMA/PVC blends have been contributed. Using regression method, linear calibration curve between PMMA mole content and peak areas of C=O groups in FTIR spectra of the blends has been found when C=O peak areas were multiplied by an appropriate factor. PMMA grafted content and total PMMA formed content in PVC-g-PMMA graft copolymers have been evaluated. The results showed that grafted PMMA content was increased since PVC was initiatly dechlorinated by NaOH solution. The grafted PMMA content and total formed PMMA content were 5.05 wt.% and 11.25 wt.% respectively when MMA monomers were grafted onto neat PVC and modified PVC molecules